Residue retention and soil matric potential-based irrigation improve productivity, energy efficiency and profitability of wheat (Triticum aestivum) - KAUR, PARMINDER; KANG, JASJIT SINGH; KAUR, JAGROOP; MANHAS, SURJIT SINGH; GUPTA, NAVEEN (The Indian Journal of Agricultural Sciences, 2026)
High energy consumption and declining profitability in wheat (Triticum aestivum L.) production following rice pose significant challenges to sustainable agriculture. Inefficient residue management practices, and traditional irrigation methods lead to excessive energy use, environmental degradation, and reduced economic returns. To address these issues, a field experiment was conducted during rabi 2021–22 and 2022–23 at Punjab Agricultural University, Ludhiana to evaluate the productivity, energetics and profitability of wheat under residue management and soil matric potential-based irrigation. The experiment was laid out in randomised complete block design comprising nine treatments of crop residue management including conventional tillage with/without rice residue, zero tillage with/without rice residue, zero tillage with rice residue and retention of wheat residue, zero tillage after partial burning of rice residue, with irrigation at 35 ± 1 kPa in all crop residue management treatments. Higher grain yield, net energy, energy use efficiency and energy productivity were obtained in zero tillage (double crop residue) + irrigation at 35 ± 1 kPa while, economic returns viz., net returns, gross returns and benefit-cost ratio were maximum under zero tillage (single crop residue) + irrigation at 35 ± 1 kPa. Principal component analysis further indicated strong positive relationships among grain yield, energy output, net energy and economic returns, with residue retention treatments showing close association with improved productivity and energy efficiency. Overall, the study suggests that zero tillage with rice residue retention combined with soil moisture potential-based irrigation scheduling (35 ± 1 kPa) is an effective strategy for improving productivity, energy efficiency and profitability of wheat grown after rice.